Blackberry beach ebook - Hannon, Irene (Hope Harbor, 2021)
Katherine Parker is on the cusp of achieving the kind of career success she'd always dreamed of. But a visit to Hope Harbor for some much-needed R&R—and an unexpected partnership with a handsome local coffee shop owner—may cause her to rethink her ambitions and open her heart to a new dream.